(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Concepts such as meditation center, amusement park, actually designed for iconic monuments like Dome, Taj Mahal, Lotus Temple, etc., commercial mall, residential or office building. The shape, design and technology itself will become internationally attracted building. The shape of the building is star shaped. The building will stand on single point of conical arms of star attached to the sphere making it look like a star. The external shell of the life star building will revolve around the structure from outside and the elevation will look as if the whole building is revolving on one single point. The technology used to make the building stand on one single point will be based on magnetic field and gravitational energy in balance with wind, rain and sun habbits. The life star building structure can be built in structural steel , Reinforced Cement Concrete , etc. This building will make use of maximum solar panels instead of glass where ever required for exterior facade taking care the aesthetics of elevation of the building. Landscape designing includes rain water harvested in underground drainage sprinklers.